OPIS ŚWIĄTYNI MĄDROŚCI BOŻEJ W KONSTANTYNOPOLU PROKOPIUSZA Z CEZAREI – MIĘDZY HISTORIOGRAFIĄ A RETORYKĄ - Garnczarska, Magdalena (Saeculum Christianum. Pismo Historyczne, 2017)
The sixth-century historian Procopius of Caesarea described the church of Hagia Sophia in Constantinople in his treatise „Περὶ κτισμάτων” (“On Buildings”). The text about Hagia Sophia is the only surviving historical source for the original Justinianic edifice before the collapse of its first dome in 558. This detailed and elaborate description of the church is an example of ekphrasis. Ekphrasis is a rhetorical technique which makes the described object visible. In this paper I will attempt to analyse how far Procopius' description is a rhetorical exercise, and how far it is a trustworthy historical source.